The risk of physical environment on the incidence of pneumonia in the Puskesmas Remu Sorong City - Pangaribuan, Sariana; Siagian, Jenni Lilis; Sanoy, Yustinus Derek; Talakua, Febri; Artafella, Agung (Institute Of Computer Science (IOCS), 2024)
Pneumonia is a respiratory infection that attacks the lungs, the World Health Organisation (WHO) recorded 2.5 million people died from pneumonia. Based on preliminary data collection, in January-June 2022 there were 17 cases and 34 controls, in the Remu Health Centre working area of Sorong City. The purpose of this study was to determine the risk of house building, house lighting, house humidity, house ventilation, and occupancy density on the incidence of pneumonia among under-fives in the Remu Health Centre working area of Sorong City. This type of research is analytic observation, with a case control design, using the odds ratio (OR) test to determine the magnitude of risk. This study was conducted in the Remu Health Centre working area of Sorong City on 22 September 22 October with a total sample of 51 children under five years old. The results showed that there was a risk, house building (OR=7.538), house lighting (OR=2.417), house humidity (OR=2.531), house ventilation (OR=3.714), occupancy density (OR=3.210), to the incidence of pneumonia. Conclusion House building, house lighting, house humidity, house ventilation area, and occupancy density are risk factors for the incidence of pneumonia among under-fives in the Remu Puskesmas working area of Sorong City.